Realistic environmental exposure to secondary PET microplastics induces biochemical responses in freshwater amphipod Hyalella azteca - Queiroz, Lucas Gonçalves; Rani-Borges, Bárbara; Prado, Caio César Achiles; Moraes, Beatriz Rocha de; Ando, Rômulo Augusto; Paiva, Teresa Cristina Brazil de; Pompêo, Marcelo (Chemistry and ecology, 2023)
Freshwater environments are especially susceptible to microplastic contamination due to their proximity to urbanised and industrial areas. Also, there is a lack of information about the effects of this pollutant on freshwaters making it difficult the conservation of these environments. Benthic species, such as the freshwater amphipod Hyalella azteca, have been superficially studied so far for evaluation of microplastic pollution. In the present study, we analyzed whether polyethylene terephthalate (PET) microplastics could lead to reduced survival of H. azteca or changes in biochemical markers (SOD, CAT, MDA, and GST) at environmentally relevant concentrations (60 and 600 particles) after 7 d of exposure. The results showed that there was no significant mortality at any of the concentrations tested. The enzyme CAT showed no variation compared to the control group at any of the concentrations. SOD, MDA, and GST were statistically different (p < 0.05). Our study demonstrated that PET MP did not affect the survival of H. azteca at environmentally relevant concentrations. However, changes in biomarkers of oxidative stress may be detected at low level of exposure (60 particles). Although survival is not affected, the macrobenthic invertebrate community may be under threat in environments where there is PET microplastic pollution.